Effects of 8 weeks of isoinertial vs. cable-resistance training on motor skills performance and interlimb asymmetries - Madruga-Parera, M.; Bishop, C.; Fort-Vanmeerhaeghe, A.; Beato, M.; Gonzalo-Skok, O.; Romero-Rodríguez, D. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study was to compare the effects of 8 weeks of isoinertial vs. cable-resistance training on motor skills performance and interlimb asymmetries in handball players. Thirty-four young male handball players (mean ± SD: age: 15.96 ± 1.39 years; height: 1.74 ± 0.73 m; body mass: 70.5 ± 13.3 kg) participated in a randomized trial. The players performed an isoinertial program using a portable flywheel device or a cable-resistance device. Performance variations and interlimb asymmetries in dominant (D) and nondominant (ND) limb means of the unilateral countermovement jump (UCMJ), the unilateral lateral jump (ULJ), the unilateral broad jump (UBJ), handball throwing (HT), change of direction speed (COD180), the linear sprint (S20), the V-CUT test, and the repeated change of direction (RCOD) were recorded. Significant interactions were shown in RCODD (p = 0.003, Eta p = 0.25), HT (p = 0.015, Eta p = 0.17) and UCMJASY (p = 0.037, Eta p = 0.13). Post-hoc testing revealed higher effect sizes in the isoinertial group (p < 0.05) for the performance improvements in RCODD (-1.35 large vs. -0.22, small) and HT (0.88, moderate vs. 0.00, trivial), in addition to interlimb asymmetry reductions in UCMJASY (-0.70 moderate vs. -0.32, small). Significant main effects of time in COD180, RCOD, UCMJ, and UBJ for both limbs (p < 0.05, from moderate to large effect size), and in ULJND (p < 0.001, large), UCMJASY (p < 0.001, moderate), V-CUT (p = 0.014, small), and HT (p = 0.015, large) were found. The effect sizes revealed greater magnitudes in the isoinertial group. In conclusion, although both resistance training programs improve players' to physical performance and reduce interlimb asymmetries, greater improvements were recorded with the isoinertial resistance training than with the cable-resistance methodology.